Multidimensional Translation in Linguistic Annotation - Chalise, Krishna Prasad (Gipan, 2017)
The core components of linguistic annotation consist of transcription, interlinear glossing and free translation. A linguistic annotation incorporates different types of translations together in itself. From one perspective, the transcription is a type of transliteration and from another perspective; it is very close to translation. Similarly, interlinear glossing is linear morpheme-to-morpheme or word-to-word translation. In the same way the free translation incorporates a variety of translations from literal to idiomatic translation.